Pythium Blight on Overseeded Turfgrass - Philip F. Harmon; Carol M. Stiles; Lawrence E. Datnoff (EDIS)
Pythium blight or cottony blight rapidly kills cool-season turfgrasses overseeded as winter cover of warm-season species. The disease can occur on bermudagrass in the summer, but disease severity on this warm-season species often is limited when compared to the damage caused to cool-season turfgrass. Pythium aphanidermatum as well as other species, such as P. torulosum, have been associated with Pythium blight of overseeded turfgrasses in Florida. This document is PP 203, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2004.